2006
DOI: 10.1074/jbc.m601702200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Principal Interaction Site of the Brf1 and Bdp1 Subunits of Saccharomyces cerevisiae TFIIIB

Abstract: The Brf1 subunit of the central RNA polymerase (pol) III transcription initiation factor TFIIIB is bipartite; its N-terminal TFIIBrelated half is principally responsible for recruiting pol III to the promoter and for promoter opening near the transcriptional start site, whereas its pol III-specific C-terminal half contributes most of the affinities that hold the three subunits of TFIIIB together. Here, the principal attachment site of Brf1 for the Bdp1 subunit of TFIIIB has been mapped by a combination of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
6
24
0
Order By: Relevance
“…Photocrosslinking studies used to analyze the interaction between TFs and the promoters of a 5S rRNA gene and a tRNA gene have shown that the Tfc4 subunit of TFIIIC associates with the region around the transcription start site (TSS), which is consistent with proximal flexibility, 20 while the 90 kDa subunit of TFIIIC, TFC6, associates with the terminator element. 47 Nagarajavel et al 10 analyzed genome-wide 'bootprints' of TFIIIC and TFIIIB in vivo, with single nucleotide resolution, using ChIP-seq.…”
Section: Tfiiic Has Adjustable Hinges and Flexibly Encompasses Trna Gmentioning
confidence: 97%
See 1 more Smart Citation
“…Photocrosslinking studies used to analyze the interaction between TFs and the promoters of a 5S rRNA gene and a tRNA gene have shown that the Tfc4 subunit of TFIIIC associates with the region around the transcription start site (TSS), which is consistent with proximal flexibility, 20 while the 90 kDa subunit of TFIIIC, TFC6, associates with the terminator element. 47 Nagarajavel et al 10 analyzed genome-wide 'bootprints' of TFIIIC and TFIIIB in vivo, with single nucleotide resolution, using ChIP-seq.…”
Section: Tfiiic Has Adjustable Hinges and Flexibly Encompasses Trna Gmentioning
confidence: 97%
“…20 Once a TFIIIB-DNA complex is formed, it is sufficient to recruit RNAP III and direct transcription, suggesting that TFIIIB is the transcription initiation factor proper for RNAP III while the others function as prerecruitment assembly factors, as was demonstrated in vitro and in vivo. 21,22 Interactions between Brf1 and the integral RNAP III subunits C34 and C17 are important for RNAP III recruitment.…”
mentioning
confidence: 90%
“…Brf1c exists mostly as a scaffold that holds together the three TFIIIB subunits (12, 26). In particular, structural analysis of the Brf1-TBP-DNA complex indicated that homology block II is positioned along the convex and lateral surfaces of TBP and that the block also interacts with Bdp1 (5,6,10,22,[26][27][28]. The homology blocks are separated by two nonconserved connecting regions that we refer to as C linkers 1 and 2 (Fig.…”
mentioning
confidence: 99%
“…TFIIIB is composed of TFIIB-related factor Brf1, TATA box binding protein TBP, and SANT domain-containing subunit Bdp1. Previous biochemical studies indicated that Brf1 and TBP cooperatively assemble onto DNA upstream of the transcription start site and Bdp1 binds to the Brf1-TBP-DNA complex mainly through its SANT domain (4)(5)(6)(7)(8)(9)(10). The TFIIIB-DNA assembly is required for subsequent Pol III recruitment and transcript initiation.…”
mentioning
confidence: 99%
“…The principal attachment sites between TBP, Brf1, and Bdp1 were determined by chopping and slicing; the N-terminal half of Brf1 and its TFIIB paralog were shown to bind to overlapping TBP sites (129); the structure of the stronger TBP-binding segment of Brf1, which is part of its C-terminal half, in complex with TBP and DNA was also solved (130). The structure, in turn, led to an in vitro mutation screen showing that the TBP-interacting Brf1 segment serves as a kind of double-sided adhesive mediating attachment of TBP to Bdp1 (131). Cellular functions are executed by spatially organized multiprotein complexes, each of whose subunits may comprise multiple domains, securing the network of interactions that determine assembly as well as function.…”
Section: Rna Polymerase IIImentioning
confidence: 99%